ANALISIS SUKU BUNGA KREDIT, CAPITAL ADEQUACY RATIO (CAR), BIAYA OPERASIONAL TERHADAP PENDAPATAN OPERASIONAL (BOPO), DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP NON PERFORMING LOAN (NPL) DI KALIMANTAN BARAT - B01110028, M. Aditya Perdana Putra (Jurnal Pembangunan dan Pemerataan, 2014)
This study aimed to examine the effect of Interest Rate, Capital Adequacy Ratio (CAR), Operating Income Operating Expenses Against (ROA), and the Loan to Deposit Ratio (LDR) of the Non-Performing Loan (NPL) as a projection of the bad loans that are in West Borneo that occurred from January 2008 to December 2011 . The data used in this study were obtained from data published by Bank Indonesia every month from January 2008 to December 2011. Data analysis technique used is multiple regression and hypothesis testing using t - statistics to test the partial regression coefficients and F - statistics to examine the effect together with a level of significance of 5%. It also performed classical assumption which include normality test, multicollinearity, and heteroscedasticity test. During the observation period of the study indicate that the data are normally distributed. Based on the test multicollinearity and heteroscedasticity test variables were not found to deviate from the classical assumptions, it indicates that the available data are qualified to use the multiple linear regression model. For the partial results of the study indicate that the variable Interest Rate, and CAR positive and significant impact on the NPL, while ROA is negative and significant effect on the NPL, and LDR positive effect but no significant effect on the NPL   Keyword         :           Non Performing Loan (NPL), Interest Rate, Capital Adequacy Ratio (CAR), Operating Income Operating Expenses Against (BOPO), and the Loan to Deposit Ratio (LDR)